ACEH: EXPLORING THE AFTERMATH OF 2004 TSUNAMI FROM GENDER DIMENSIONS - Sorang Afril Srihayati Saragih (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2017)
This paper aims to analyse the greatest gender-specific dimensions toward women in the case of the tsunami that hit Aceh Province in Indonesia in 2004. Using three gender dimensions, which are gender identity, gender structure and gender symbolism, it argues that this catastrophe was not gender-neutral and its impacts could be shown in four conditions of women; which were womenâ€™s worsened insecurity and vulnerability, the feminization of poverty, the presence of â€œtsunami marriageâ€, and the reinforced gendered roles. The concept of â€˜intersectionalityâ€™ is useful to show the heterogeneous identity of women and how they were impacted by the disastrous event. It concludes that the 2004 tsunami brought many changes in the lives of both men and women in Aceh and worsened the inequalities between them. Keywords: Aceh, women, tsunami, gender dimensions Abstrak Tulisan ini bertujuan untuk menganalisis dimensi-dimensi terbesar yang spesifik-gender dalam kasus tsunami yang melanda Provinsi Aceh di Indonesia pada tahun 2004. Menggunakan tiga dimensi gender, yakni identitas gender, struktur gender dan simbolisme gender, tulisan ini menyatakan bahwa bencana ini tidaklah netral-gender dan dampaknya dapat ditunjukkan dalam empat kondisi perempuan; yaitu ketidakamanan dan kerentanan perempuan yang semakin memburuk, feminisasi kemiskinan, munculnya â€œpernikahan tsunamiâ€, dan peran-peran berbasis gender yang semakin menguat. Konsep â€˜interseksionalitasâ€™ berguna dalam memperlihatkan identitas heterogen perempuan dan bagaimana mereka terkena imbas dari peristiwa bencana tersebut. Tulisan ini berkesimpulan bahwa tsunami di tahun 2004 itu membawa banyak perubahan dalam hidup laki-laki dan perempuan di Aceh, serta memperburuk ketimpangan di antara mereka. Kata Kunci: Aceh, perempuan, tsunami, dimensi gender